Fenofibrate Inhibited the Differentiation of T Helper 17 Cells In Vitro - Zhou Zhou; Weiliang Sun; Ying Liang; Yanxiang Gao; Wei Kong; Youfei Guan; Juan Feng; Xian Wang (PPAR Research)
Uncontrolled activity of T cells mediates autoimmune and inflammatory diseases such as multiple sclerosis, inflammatory bowel diseases, rheumatoid arthritis, type 1 diabetes, and atherosclerosis. Recent findings suggest that enhanced activity of interleukin-17 (IL-17) producing T helper 17 cells (Th17 cells) plays an important role in autoimmune diseases and inflammatory diseases. Previous papers have revealed that a lipid-lowering synthetic ligand of peroxisome proliferator-activated receptor α (PPARα), fenofibrate, alleviates both atherosclerosis and a few nonlipid-associated autoimmune diseases such as autoimmune colitis and multiple sclerosis. However, the link between fenofibrate and Th17 cells is lacking. In the present study, we hypothesized that fenofibrate inhibited the differentiation of Th17 cells. Our results showed that fenofibrate inhibited transforming growth factor-β (TGF-β) and IL-6-induced differentiation of Th17 cells in vitro. However, other PPARα ligands such as WY14643, GW7647 and bezafibrate did not show any effect on Th17 differentiation, indicating that this effect of fenofibrate might be PPARα independent. Furthermore, our data showed that fenofibrate reduced IL-21 production and STAT3 activation, a critical signal in the Th17 differentiation. Thus, by ameliorating the differentiation of Th17 cells, fenofibrate might be beneficial for autoimmunity and inflammatory diseases.